Demand-side and supply-side factors for accelerating varietal turnover in smallholder soybean farms - Nuthalapati, Chandra S.; Kumar, Anjani; Birthal, Pratap S.; Sonkar, Vinay K. (Elsevier, 2024)
The rapid growth of soybean cultivation in the world augurs well for achieving SDG2 of promoting sustainable agriculture, ending hunger, achieving food security, and improving nutrition. India started promoting soybean cultivation in the 1970s to combat dietary protein deficiencies and augment smallholders' incomes. However, soybean yield remains low and plateaued at one ton per hectare for the past three decades. This paper leverages a large primary dataset and explores the speed of soybean varietal change by applying survival functions and analyzing determinants of varietal turnover time employing a dynamic framework and harnessing duration analysis. The results show that adopting leading soybean varieties has reached saturation and that policy intervention can have an immediate impact. The weighted average age of soybean varieties in farmers' fields is relatively high at 16 years, implying a slower varietal change rate. The lack of improved varieties with desirable traits, poor information flow, and growers’ preference for traits beyond yield-hamper faster varietal substitution. Further, analysis indicates regional variations in driving the speed of varietal replacement. The findings have significant implications for spurring soybean yields through investments in varietal development, leveraging modern molecular methods for long juvenility and photo-insensitivity, disseminating information, and institutional changes enabling the private sector participation in crop breeding.